PENGGUNAAN SEMIOTIKA DALAM PENAFSIRAN MITOLOGI JAWA: KAJIAN TENTANG PRESEKTIF SIMBOL DALAM TRADISI JAWA - Ferdiansyah, Panji; Rumilah, Siti (Wacana: Jurnal Penelitian Bahasa, Sastra dan Pengajaran, 2025)
This study examines the use of semiotics in interpreting Javanese mythology through symbols and icons in folktales. The research employed a qualitative approach with data analysis from various folktales. The findings reveal the existence of symbols and icons that carry Javanese cultural meanings. This interpretation provides a deeper understanding of mythology and enriches the understanding of Javanese culture. These findings contribute significantly to the fields of literature and semiotics.